Radical adaptation in agriculture: tackling the roots of climate vulnerability - Vermeulen, Sonja J.; Mason M; Dinesh, Dhanush; Adolph, Barbara (2015)
As climate change pushes livestock, crop and tree production systems towards new realities, societies may seek more comprehensive solutions. Examples of truly radical adaptation — pre-emptive actions at scale that address the root causes of climate risks and reduce climatic footprint — are still to emerge in agriculture globally. Yet there is much to learn from countries, communities and industries that are transforming agricultural livelihoods. Case studies show that local experience, combined with external knowledge, provide the platform for positive change. From these examples, we present nine lessons on how to shift towards a more radical pathway for adaptation. The levers for new behaviours can be surprisingly simple, although addressing root causes may require more fundamental reforms. Looking ahead, radical adaptation can guide practical actions towards a well-adjusted future for food and farming.